2010
DOI: 10.1016/j.bbrc.2010.08.117
|View full text |Cite
|
Sign up to set email alerts
|

Migration defects by DISC1 knockdown in C57BL/6, 129X1/SvJ, and ICR strains via in utero gene transfer and virus-mediated RNAi

Abstract: Disrupted-in-Schizophrenia 1 (DISC1) is a promising genetic risk factor for major mental disorders. Many groups repeatedly reported a role for DISC1 in brain development in various strains of mice and rats by using RNA interference (RNAi) approach. Nonetheless, due to the complexity of its molecular disposition, such as many splice variants and a spontaneous deletion in a coding exon of the DISC1 gene in some mouse strains, there have been debates on the interpretation on these published data. Thus, in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…In addition, other Disc1 RNAi tools that confer a defective phenotype in the 129 and outbred ICR strain backgrounds require verification of the knockdown specificity. Some groups have reported that Disc1 knockdown in the brains of 129 and outbred ICR mice leads to extensive disruption of cortical migration and adult neurogenesis 14,[17][18][19] . One of the Disc1 shRNAs used in these studies is shRNA-D1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other Disc1 RNAi tools that confer a defective phenotype in the 129 and outbred ICR strain backgrounds require verification of the knockdown specificity. Some groups have reported that Disc1 knockdown in the brains of 129 and outbred ICR mice leads to extensive disruption of cortical migration and adult neurogenesis 14,[17][18][19] . One of the Disc1 shRNAs used in these studies is shRNA-D1.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was performed according the published protocol with minor modifications (24,25). Briefly, pregnant C57BL/6 mice were anesthetized at embryonic day 14.5 (E14.5) by isoflurane, and shRNA plasmids (control or DISC1 shRNA) together with CAG::Venus vector were injected into the bilateral ventricles.…”
Section: Methodsmentioning
confidence: 99%
“…6A). In this model, by in utero electroporation, DISC1 shRNA is selectively targeted to the cells in a lineage of the pyramidal neurons in the layer II/III of the prefrontal cortex (24,25). Among the PAK inhibitors tested above, FRAX486 displayed the highest penetrance of blood-brain barrier (Fig.…”
Section: Pak Inhibitors Reverse Preexisting Dendritic Spine Shrinkagementioning
confidence: 99%
“…Furthermore, the present study precludes potential off-target effects elicited by an RNAi construct 12, 13 that was used to show the involvement of DISC1 in progenitor cell proliferation and neuronal migration: The DISC1 RNAi construct does not affect the migration of Disc1 LI mice in which the target sequences of RNAi were genetically depleted (Supplementary Figure 3). …”
Section: Critical Roles Of Disc1 In Early Brain Development: Further mentioning
confidence: 98%